2009
DOI: 10.1111/j.1467-9280.2008.02261.x
|View full text |Cite
|
Sign up to set email alerts
|

The Irony of Harmony

Abstract: Positive intergroup contact has been a guiding framework for research on reducing intergroup tension and for interventions aimed at that goal. We propose that beyond improving attitudes toward the out-group, positive contact affects disadvantaged-group members' perceptions of intergroup inequality in ways that can undermine their support for social change toward equality. In Study 1, participants were assigned to either high- or low-power experimental groups and then brought together to discuss either commonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
220
3
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 463 publications
(278 citation statements)
references
References 28 publications
11
220
3
10
Order By: Relevance
“…Specifically, we have provided the first empirical demonstration that perspective taking-regardless of the specific form (perspective-taking-self vs. perspective-takingother)-can positively alter automatic intergroup evaluations. We also have demonstrated that, unlike other bias-reduction strategies Saguy et al, 2009), perspective taking does not blind perceivers to the realities of interracial disparities. Not only did it weaken associations between Blacks and general negativity (Whites and general positivity), but it also strengthened associations between Blacks and oppression-related concepts (Whites and privilege-related concepts).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Specifically, we have provided the first empirical demonstration that perspective taking-regardless of the specific form (perspective-taking-self vs. perspective-takingother)-can positively alter automatic intergroup evaluations. We also have demonstrated that, unlike other bias-reduction strategies Saguy et al, 2009), perspective taking does not blind perceivers to the realities of interracial disparities. Not only did it weaken associations between Blacks and general negativity (Whites and general positivity), but it also strengthened associations between Blacks and oppression-related concepts (Whites and privilege-related concepts).…”
Section: Discussionmentioning
confidence: 94%
“…For instance, although focusing on intergroup commonalities has long been argued to promote more positive intergroup evaluations, focusing solely on commonalities can limit motivation for actual social change by desensitizing people to the persistence of interracial disparities (Dovidio, Gaertner, & Saguy, 2009;Saguy, Tausch, Dovidio, & Pratto, 2009). If perspective taking, which has been shown to increase perceptions of intergroup commonality (Galinsky, Ku, & Wang, 2005;Galinsky & Moskowitz, 2000;Galinsky, Wang, & Ku, 2008), is susceptible to this unintended side effect, its general value as a strategy for navigating interracial contexts could be limited.…”
Section: Perspective Taking and The Attenuation Of Contemporary Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, intergroup contact has been shown to lead to potentially unfavorable outcomes for immigrants at the collective level, since personal contacts across group boundaries may deflect attention from structural inequality between disadvantaged and privileged ethnic groups. As a result, harmonious intergroup contact may paradoxically decrease support for political measures addressing these inequalities (Saguy, Tausch, Dovidio, & Pratto, 2009;Wright & Lubensky, 2009). Contact research should therefore go beyond the analysis of the impact of contact at the individual level, and include analyses that demonstrate how contact patterns relate to political outcomes such as institutional discrimination and immigration policies and more broadly to social change.…”
Section: Perceived Threat and Intergroup Contactmentioning
confidence: 99%